Production of Paper Pulp Using Sisal Fiber Waste from Sisal Spinning Processes - Bosco, Mtweve; Mbise, Ekael; Minja, Rwaichi J. A. (Tanzania Journal of Engineering and Technology, 2022)
Disposal of large volumes of textile waste is an escalating problem for textile industries. Sisal spinning industry is the one of the textile industries releasing large volumes of textile waste in the landfills. The rising costs, and reduction of available space together with increasing stringent environmental measures are making burying and land filling of textile waste, a declining option. This study therefore explores recycling options where the potential of using sisal fiber waste produced during sisal spinning processes as raw materials for the production of paper pulp was investigated. Sampling was done at 21stCentury Holdings Limited allocated at Chang ' ombe industrial street Dar es Salaam mainly dealer of sisal yarns production. Materials were prepared and cut into small pieces of about ½ inches to reduce the fiber into unit lengths so as to achieve pulping required performance. Pulping process was achieved through Soda pulping techniques with two different effective alkali charges (EA-20% and EA-24%) for 240 minutes under maximum temperature 140 —¦C, and liquor to fiber ratio 4:1by using Mathis Labomat dyeing Machine. The kappa number obtained was (25.5, 34.5) for material treated under EA 24% and EA 20% respectively, Percentage pulp yield were (47.1, 54.4) for EA 24% and EA20% pulp respectively. Freeness (630CFS, 555CSF) after refining at 4500rpm. Finally, the resulting pulp was used for hand sheet making and the sheets were tested for their mechanical properties; Grammage (61.1, 61.1) g/m2, Tensile index (9.9, 22.3) Nm/g, Tear index (13.3, 17.4) Nm2/g, burst index (1.7, 3.7 and 1.6) k.pa.m2/g and Elongation at break (2.02, 2.22) % for EA24% pulp, EA20% pulp respectively. The findings shows that sisal fiber wastes have a promising potential for paper pulp production compared to other non-wood raw material. Keywords: Sisal fibber waste, Effective alkali percentages (EA%), Freeness (CSF), Pulp yield, Kappa number, Elongation at break, Burst index, Tensile index, Tear index.